Mec1-mediated Atg9 phosphorylation regulates the PAS recruitment of Atg9 vesicles upon energy stress - Siyu Fan; Shuling Dong; Weijing Yao; Yi Zhang; Mingzhu Fan; Shan Feng; Choufei Wu; Liqin Zhang; Cong Yi (Proceedings of the National Academy of Sciences, 2025)
Mec1 plays an essential role in both the DNA damage response and glucose starvation–induced autophagy. We recently reported that Mec1 regulates glucose starvation–induced autophagy through its direct binding to Atg13. However, the role of Mec1’s kinase activity in autophagy remains unclear. In this study, we demonstrate that the kinase activity of Mec1 is required for glucose starvation–induced autophagy by regulating the phagophore assembly site (PAS) recruitment of Atg9 vesicles. Mechanistic and functional analyses identified Atg9 as a direct phosphorylation substrate of Mec1, with phosphorylation occurring at the S35, T203, and T243 sites. Mutations at these sites reduce the association of Atg9 with Atg17, Atg23, and Atg27, thereby impairing the PAS recruitment of Atg9 vesicles. Notably, we found that the Mec1–Atg13 binding is a prerequisite for the phosphorylation of Atg9 by Mec1. Furthermore, Mec1-mediated phosphorylation of Atg9 is also crucial for the PAS recruitment of Atg9 vesicles in response to DNA damage. We thus propose that Mec1’s kinase activity regulates the PAS recruitment of Atg9 vesicles by phosphorylating Atg9 in response to energy stress and DNA damage.